Associations between cognition and neuropsychiatric symptoms in people with dementia: Protocol for a systematic review and multilevel meta‐analysis: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Sabates, Julieta M.; Lampit, Amit; Malmberg Gavelin, Hanna; Loi, Samantha M.; Brodtmann, Amy; Chong, Terence W.H.; Goh, Anita M.Y.; Lautenschlager, Nicola T.; Bahar‐Fuchs, Alex
Abstract: Background: Neuropsychiatric symptoms (NPS), including depression, anxiety, apathy, aggression and agitation, among others, are highly prevalent in people with dementia (PWD), and are associated with lower quality of life and greater caregiver distress 1 . Over recent years there has been a proliferation of research aimed at exploring the cause of NPS and the relationships between them and impairment in specific cognitive abilities. Despite this interest, previous work has been limited mostly to cross‐sectional and longitudinal studies and, until now, systematic reviews on this topic have tended to focus on one symptom or type of dementia. The specific associations between cognitive impairment and NPS in PWD regardless of aetiology are, therefore, still poorly understood. Furthermore, no previous study has investigated whether these associations vary between younger and late‐onset dementia. The aim of our research is to investigate the specific links between cognition and NPS in PWD, and explore the moderators of these relationships, including dementia aetiology and age of onset. This review forms a first step in the design of a novel mHealth intervention for NPS in PWD which will be informed by its findings. Method: We will search relevant databases for observational and interventional studies investigating these associations. We will convert outcome data from studies to standardised mean difference (SMD, calculated as Hedges' g) 2 with 95% confidence interval of difference in cognitive performance between the exposure groups, correlation coefficient or odds ratios. We will synthesise the data by conducting multilevel random effects analyses. Results: The findings from this review will make an important contribution to research by improving the knowledge about the correlates of NPS. Conclusion: Results are likely to have important implications for the management and treatment of NPS. Appelhof, B., Bakker, C., Zwijsen, SA., Smalbrugge, M., Verhey, F. R., de Vugt, M. E., … & Koopmans, R. T. (2017). The determinants of quality of life of nursing home residents with young‐onset dementia and the differences between dementia subtypes. Dementia and geriatric cognitive disorders, 43 (5‐6), 320‐329. Rosenthal, Robert, H. Cooper, and L. Hedges. "Parametric measures of effect size." The handbook of research synthesis 621 (1994): 231‐244.